Stabilisasi Tanah Ekspansive dengan Menggunakan Tanah Putih untuk Tanah Dasar di Daerah Godong Kabupaten Grobogan Jawa Tengah - Wardani, Sri Prabandiyani Retno; Muhrozi, Muhrozi; Setiaji, Andi Retno Ari; Riwu, Danny R (MEDIA KOMUNIKASI TEKNIK SIPIL, 2018)
Problematic soils such as expansive soils are common in Indonesia. There are several methods to overcome the damage caused by expansive soil, such as by mixing the soil with additives. Some researchers have conducted research by mixing additives into expansive soil (cement, lime, fly ash etc), which work to increase soil strength and reduce swelling. Considering that the people in Buraen Village of Kabupaten Kupang use white soil as a substitute for cement, where the white soil has chemical constituents almost the same as those owned by cement, and contain CaO as it has lime, it is necessary to do research to determine the effect of white soil on physical and mechanical properties of expansive soil, so it can be used as an additive. This research was conducted at Soil Mechanics Laboratory, Civil Engineering Department, Engineering Faculty, Diponegoro University, Semarang.with soil sample from Godong, Central Java and white soil in Buraen Village of Kupang Regency, which purpose to find out the change of physical and mechanical properties of expansive soil that have been given some variation of mixture of white soil  to the dry weight of the soil, with optimum moisture content from standard Proctor test results. The results of this study indicate that white soil can be used as an additive and the use of OMC for mixing is the OMC of expansive soil.